Planos de saneamento de Belém (1980 a 2015): racionalidades, mudanças institucionais, intersetorialidade e participação social - Rafael Caldeira Magalhaes (2018)
The study evaluated the Belém's sanitation plans in the years 1980, 2004 and 2015, to understand the dominant rationalities, to know the institutional changes from the historical antecedents and the analysis of public policies, to interpret the interests of the social actors with regard to the conception of sanitation and the insertion of the principles of intersectoriality and social participation. The data collection procedures consisted in the search for normative documents that make up the Belém Plan 2000 (elaborated in 1980), the Metropolitan Plan of Water and Sewage of Belém (2004) and the Municipal Plan of Basic Sanitation of Belém (2015); and semi-structured interviews with the social actors who participated in at least one of these three experiences. Content analysis was performed, which allowed the interpretation of the plans from the categories of rationality, public policy and specific interests of social actors. The results show that normative rationality was dominant in the Belém Plan 2000 and in the most current sanitation plan; this normative planning hinders the intersectoriality with the public policies of health and environment that could contribute with benefits for both urban and rural sanitation; promotes normative participation, that is, it meets legal requirements without guaranteeing the process of legitimation and validation by society, with processes of weakening civil society and depoliticizing planning processes. With the preparation of the Metropolitan Water and Sewage Plan of Belém (2004), an experience emerged from strategic rationality, which represented a significant advance in the organization and provision of sanitation services, and expanded social participation in a technical and political. With the elaboration of the municipal plan of 2015, it was realized that the participation of civil society diminished as a result of the return of normative rationality. The latter plan did not consider interests that place access to water supply and sewage services as a human right, nor does it recognize the hydrossocial mechanisms that make public sanitation policy the natural characteristics. The research also showed that the principle of intersectoriality was not concretely inserted in the sanitation plans of Belém evaluated with normative rationality, but a significant part of the interviewees proposed as an integration of knowledge and between sectoral policies, but that have positive impacts in the real life of the populations that are neglected by the provision of sanitation services or have it in poor quality.